Effectiveness of eHealth Tools for Hip and Knee Arthroplasty: A Systematic Review - Mohammadi, Somayyeh; Miller, William C.; Wu, Julia; Pawliuk, Colleen; Robillard, Julie M. (Frontiers in Rehabilitation Sciences, 2021)
Objective. This study aimed to compare the effectiveness and costs of eHealth tools with usual care in delivering health-related education to patients’ undergoing total hip or knee arthroplasty due to osteoarthritis. Data Sources. Six electronic databases were searched to identify randomized controlled trials and experimental designs (randomized or not) examining the effect of eHealth tools on pre- or postoperative care. Only manuscripts written in English were included. In the current study, no specific primary or secondary outcomes were selected. Any study that investigated the impacts of eHealth tools on hip or knee arthroplasty outcomes were included. Review methods. Two researchers reviewed all titles and abstracts independently and in duplicate. Two researchers also conducted full-text screening and data extraction from the 26 selected articles. Results. The data were descriptively reported, and themes could emerge from each outcome. Two researchers separately assessed the Risk of Bias for each paper using the Cochrane risk of bias assessment tool. The majority of studies evaluated the impact of eHealth tools on physical (n = 23) and psychosocial outcomes (n = 19). Cost-related outcomes were measured in 7 studies. eHealth tools were found to be equivocal to usual care, with few studies reporting statistically significant differences in physical or psychosocial outcome measures. However, cost-related outcomes showed that using eHealth tools is more cost-effective than usual care. Conclusions. This review demonstrated that eHealth tools might be as effective as usual care, and possibly more cost-effective, a crucial implication for many overly burdened health care systems.